Better Students Ask More Questions.
Use the fundamental Theorem of Calculus to find ` d/(dx) int_(-x)^x ((z-1)/(z+2)) dz`
1 Answer | add yours
`d/(dx) int_(-x)^x ((z-1)/(z+2)) dz`
Rewrite this as
`d/(dx) int_(-x)^x (1 - 3/(z+2)) dz = d/(dx) ( z - 3ln(z+2))|_(-x)^x`
`= d/(dx) ( x - 3ln(x+2) - (-x - 3ln(2-x)))`
`= d/(dx) 2x - d/(dx) (3ln(x+2)) +d/(dx) (3ln(2-x))`
` ``= 2 - 3/(x+2) - 3/(2-x)` answer
Posted by mathsworkmusic on November 28, 2012 at 1:59 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.